HAK PENDIDIKAN BAGI PENYANDANG DISABILITAS DALAM PERSPEKTIF HUKUM PERDATA DAN HAK ASASI MANUSIA - Ikbar Maulana Malik (Asy-Syari'ah, 2019)
Abstract: Law regulates all aspects of life, one of which is education rights. Education is given to humans not only for non-disabled people (normal) but disability has the right of education because this indicates that there is justice and in order to achieve the objectives of the rule of law, namely to educate the life of the nation. However, there are several issues or cases that still seem to ignore the right of education for persons with disabilities. This study uses a method in the form of Descriptive Analysis, the type of data carried out is qualitative. Then the data source used is primary. Furthermore, in the technique of data collection is done by searching in books, articles, journals and other literacy. Then analyze the data by understanding and formulating conclusions on the problems used in the formulation of the problem. The results of this study are that there are still several factors that make the cause of not fulfilling the right to education for persons with disabilities then in the review of civil law and human rights very supportive for the implementation of the right to education for persons with disabilities given fully and thoroughly.Abstrak: Hukum mengatur segala aspek kehidupan salah satunya hak pendidikan. Pendidikan diberikan kepada manusia bukan hanya bagi non disabilitas (normal) tetapi disabilitaspun mempunyai hak pendidikan sebab hal ini menandakan ada keadilan dan demi mencapai tujuan Negara hukum yaitu mencerdaskan kehidupan bangsa. Namun ada beberapa isu atau kasus yang masih terkesan tidak memperdulikan hak pendidikan bagi penyandang disabilitas. Penelitian ini menggunakan metode berupa Deskriptif Analisis, Jenis data yang dilakukan bersifat kualitatif. Kemudian Sumber data yang di pakai yaitu primer Selanjutnya dalam tehnik pengumpulan data dilakukan dengan cara mencari dalam buku-buku, artikel, jurnal dan literasi lainnya. Kemudian dilakukan analisis data dengan memahami dan merumuskan kesimpulan terhadap masalah yang dijadikan dalam perumusan masalah. Hasil dari penelitian ini adalah masih ada beberapa faktor yang menjadikan sebab tidak terpenuhinya secara efektif tentang hak pendidikan bagi penyandang disabilitas kemudian dalam tinjauan hukum perdata dan Hak Asasi Manusia sangat mendukung atas implementasi hak pendidikan bagi penyandang disabilitas diberikan secara penuh dan menyeluruh.